Effect of sole or combined administration of nitrate and 3-nitro-1-propionic acid on fermentation and Salmonella survivability in alfalfa-fed rumen cultures in vitro. (April 2017) - Correa, Alejandro Castañeda; Trachsel, Julian; Allen, Heather K.; Corral-Luna, Agustin; Gutierrez-Bañuelos, Hector; Ochoa-Garcia, Pedro Antonia; Ruiz-Barrera, Oscar; Hume, Michael E.; Callaway, Todd R.; Harvey, Roger B.; Beier, Ross C.; Anderson, Robin C.; et al.
Highlights: Nitrate and 3-nitro-1-propionate are potent inhibitors of rumen methanogenesis. These inhibitors decreased digestion of alfalfa added as fermentative substrate. Nitrate, but not 3-nitro-1-propionate, promoted growth of pathogenic Salmonella . Nitrate-caused enrichment of Salmonella was prevented by 3-nitro-1-propionate. Abstract: Ruminal methanogenesis is a digestive inefficiency resulting in the loss of dietary energy consumed by the host and contributing to environmental methane emission. Nitrate is being investigated as a feed supplement to reduce rumen methane emissions but safety and efficacy concerns persist. To assess potential synergies of co-administering sub-toxic amounts of nitrate and 3-nitro-1-propionate (NPA) on fermentation and Salmonella survivability with an alfalfa-based diet, ruminal microbes were cultured with additions of 8 or 16 mM nitrate, 4 or 12 mM NPA or their combinations. All treatments decreased methanogenesis compared to untreated controls but volatile fatty acid production and fermentation of hexose were also decreased. Nitrate was converted to nitrite, which accumulated to levels inhibitory to digestion. Salmonella populations were enriched in nitrate only-treated cultures but not in cultures co- or solely treated with NPA. These results reveal a need for dose optimization to safely reduce methane production with forage-based diets.